Quantitative assessment of brain iron by R2* relaxometry in patients with cervical dystonia. Issue 10 (30th July 2015) - Aschermann, Zsuzsanna; Perlaki, Gabor; Orsi, Gergely; Nagy, Szilvia Anett; Horvath, Andrea; Bone, Beata; Bihari, Katalin; Acs, Peter; Janszky, Jozsef; Komoly, Samuel; Bogner, Peter
Abstract Background The pathophysiology of cervical dystonia is poorly understood. Increased brain iron deposition has been described in different movement disorders. Our aim was to investigate brain iron content in patients with cervical dystonia, using R2* relaxation rate, a validated MRI marker of brain iron level. Methods Twelve female patients with primary focal cervical dystonia (mean age: 45.4 ± 8.0 years) and 12 age‐matched healthy female subjects (mean age: 45.0 ± 8.0 years) underwent 3T MRI to obtain regional R2* relaxation rates of the thalamus, caudate nucleus, putamen, and globus pallidus (GP). Regions of interest were delineated automatically on T1‐weighted MRIs. Results R2* values in the putamen were positively correlated with age. Patients with cervical dystonia showed elevated R2* values in the GP. Conclusions This pilot study provides the first quantitative support for increased brain iron deposition in cervical dystonia. Further studies are needed to explore the implications of this finding.